RARE CASE OF CONGENITAL STENOSIS OF PREPUTIAL ORIFICE IN A PUP AND ITS SURGICAL CORRECTION - Shafiuzama, Mohd; Simon, M Shiju; Sooryadas, S; Kumar , R Suresh (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Congenital preputial stenosis is relatively uncommon in dogs (Sarierler and Kara, 1998). Preputial stenosis leads to small or absence of preputial opening leading to phimosis. Congenital phimosis is usually accompanied by a distended prepuce and inability to urinate normally. Urine may often be passed only in drops or as a thin stream (Johnston and Archibald , 1984). There may be preputial retension of urine resulting in balanoposthitis and ulceration of the affected area (Proeschold, 1977). Surgical enlargement of the preputial orifice and correction of the primary condition successfully alleviate the problem.
Keywords: RARE CASE; SURGICAL